Extinction in the Postcolony: Review of Juno Salazar Parreñas, Decolonizing Extinction: The Work of Care in Orangutan Rehabilitation - O'Key, Dominic (Humanimalia, 2022)
Review of Juno Salazar Parreñas, Decolonizing Extinction: The Work of Care in Orangutan Rehabilitation. Experimental Futures. Durham, NC: Duke University Press, 2018. 288 pp.; 7 illus. 26.95 (pb).